The Determinants Of Credit Spreads Of Corporate Bonds In China: The Interaction Effects Of Firm Size And The Level Of Financial Development - Kang, Weijing (2024)
In the context of the evolving economic landscape, understanding the factors influencing credit spreads on corporate bonds is crucial for ensuring the robust and sustainable development of bond markets and China's real economy. This research utilizes data from listed Chinese companies from 2011 to 2020. Employing the dynamic panel one-step system Generalized Method of Moments (GMM), the study aims to estimate dynamic models of credit spreads for corporate bonds. Specifically, it explores the impact of digital finance development, corporate governance, economic policy uncertainty, and social trust on credit spreads. The key findings indicate a significant inverse relationship between the level of digital finance development and the credit spreads of corporate bonds. Notably, the depth of digital finance usage substantially negatively influences credit spreads. Corporate governance emerges as a crucial factor affecting credit spreads, with ownership concentration, state ownership of enterprises, the proportion of independent directors, executive compensation, and the quality of information disclosure showing significant negative associations. However, board size and CEO duality significantly positively impact credit spreads. Additionally, economic policy uncertainty is positively associated with credit spreads, indicating that increased uncertainty in monetary or fiscal policies leads to higher credit spreads. Social trust also plays a crucial role, showing a significant negative impact on credit spreads, implying that the informal system within listed companies influences credit spreads.